Crashworthiness Analysis of the Impact Modules of Indonesian High-Speed Train Considering EN 15227 - Syaifudin, Achmad; Depari, Yohanes Pringeten Dilianto Sembiring; Handoko, Yunendar Aryo; Permana, Adhi Dharma; Hendrato; Halfina, Beny; Valentino, Jean Mario (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
A crashworthiness structure is being developed for the passive safety system of the Indonesian High-speed Train design. It is made up of an anti-climber, a crash buffer, and a honeycomb in sequential arrangement. The issue addressed in this research is the need for thorough verification of the design of impact modules and the supporting frame for compliance with the EN 15227 standard. The finite element method approach is used to analyze the feasibility of a collision in a high-speed train’s passive safety system. The geometry of the finite element model is constructed as a surface element and refers to the model designed by the National Research and Innovation Agency (BRIN) and the Indonesian Railways Company (PT. INKA). In accordance with the train design plan, aluminum 6005A-T6 is implemented. Simulations were conducted at initial velocities of 10 m/s using the LS-DYNA solver. The time interval during which the velocity changes is considered the time when the kinetic energy of the collision is completely absorbed. The simulation results indicate that the kinetic energy can be effectively absorbed by the crash module and the mask-of-car frame, as long as the initial contact between the trains occurs at the anti-climber. The impact kinetic energy stored in the crash buffer system is 63%, equivalent to 959 kJ, while the remaining 37%, amounting to 561 kJ, is absorbed by the cab and honeycomb frame structure. Thus, the crash structure being developed complies with the crashworthiness standard.